An updated and annotated checklist of the Dolichodoridae (Nematoda: Tylenchoidea) of Iran - Ghaderi, Reza; Karegar, Akbar; Niknam, Gholamreza (Zootaxa, 2014)
The list of plant parasitic nematodes of the family Dolichodoridae, known from Iran, is updated. 81 species belonging to 13 genera and three subfamilies are included in the list. Data for 29 species are added, of which seven species viz. Neodolichorhynchus phaseoli, Pratylenchoides crenicauda, P. erzurumensis, P. utahensis, Scutylenchus paniculoides, Trophurus impar and Tylenchorhynchus variannus are new records for the Iranian nematofauna. The list of species, further information on their morphometrics, references, referring to full or partial descriptions, associated plants, geographical distribution and some taxonomic remarks are provided. More detailed studies on some doubtful populations are proposed. The information on the taxonomic position of species in different classification schemes, as well as, the tendency of the species to certain climatic condition or ecological niche are provided. Challenges on the reliable identification of this group of nematodes in Iran are discussed and finally, suggestions were proposed for future studies.